Exposure to psychotropics in the French older population living with dementia: a nationwide population‐based study. (29th May 2016) - Breining, Alice; Bonnet‐Zamponi, Dominique; Zerah, Lorène; Micheneau, Carole; Riolacci‐Dhoyen, Nathalie; Chan‐Chee, Christine; Deligne, Jean; Harlin, Jean‐Marc; Boddaert, Jacques; Verny, Marc; Leperre‐Desplanques, Armelle
Abstract : Background: Little is known about the level of psychotropic chronic exposure in all patients living with dementia. The aim of the study was to quantify chronic psychotropic exposure in older adults with dementia compared with the general population of the same age. Methods: This prospective cohort study was conducted in France between 2009 and 2011. Aged at least 65 years, 10, 781, 812 individuals (440, 215 of them with dementia) either community based or nursing home residents were included. The numbers of single or combined prescriptions, per year for antipsychotics, antidepressants, anxiolytics, or hypnotics were measured. Results: Of patients with dementia, 15.5% are exposed to antipsychotics compared with 2.2% of the age‐matched population (relative risk [ RR ] = 6.44, 95% confidence interval [CI] [6.39−6.48]), 39.5% to antidepressants compared with 12.6% ( RR  = 4.10, 95% CI [.4.07–4.12]), and 39.6% to anxiolytics or hypnotics compared with 26.9% ( RR  = 1.74, 95% CI [1.72–1.75]). Among older adults with dementia, 13.8% simultaneously consumed at least three psychotropics. All class age of older patients with dementia is more exposed to all psychotropics except for long‐acting benzodiazepines. During the study period, chronic anxiolytic/hypnotic and antipsychotic exposure slightly decreased in population with dementia while chronic exposure to antidepressant drugs tended to increase. Conclusion: This nationwide, population‐based, drug‐used study showed for the first time that older patients with dementia are chronically overexposed not only to antipsychotics but also to psychotropics.